2007
DOI: 10.1021/pr070311+
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Overgrowth Affects Urinary Proteome Analysis:  Recommendation for Centrifugation, Temperature, Duration, and the Use of Preservatives during Sample Collection

Abstract: Bacterial overgrowth is one of the major concerns in collection and storage of biofluids, particularly 24-h urine. However, there is no previous systematic analysis of effects of bacterial overgrowth on urinary proteome analysis, and necessity, type, and appropriate concentration of preservatives to prevent bacterial overgrowth in the urine remain unclear. We, therefore, performed such systematic evaluation. Pooled normal urine was either centrifuged at 1500 g (to remove cell debris) or uncentrifuged. The samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 22 publications
1
52
0
Order By: Relevance
“…Prior to the use of MALDI-TOF MS for the diagnosis of urinary tract infections (UTIs), the presence of blood and bacteria in the urine was known to interfere with urinary proteomic analysis, specifically altering key peptide mass signals in the sample (299). Additional studies similarly suggested that bacterial overgrowth of the urine could hamper proteomic analysis and recommended that samples be centrifuged and stored immediately at 4°C and have boric acid or NaN 3 added to prevent bacteria from overgrowing (300). It remains to be seen which specimen handling conditions are necessary for optimal identification of bacteria in urinary samples, as higher bacterial burdens within the specimen could potentially simplify the detection of the bac-teria in urine samples at the expense of the rest of the urinary proteome.…”
Section: Urinementioning
confidence: 99%
“…Prior to the use of MALDI-TOF MS for the diagnosis of urinary tract infections (UTIs), the presence of blood and bacteria in the urine was known to interfere with urinary proteomic analysis, specifically altering key peptide mass signals in the sample (299). Additional studies similarly suggested that bacterial overgrowth of the urine could hamper proteomic analysis and recommended that samples be centrifuged and stored immediately at 4°C and have boric acid or NaN 3 added to prevent bacteria from overgrowing (300). It remains to be seen which specimen handling conditions are necessary for optimal identification of bacteria in urinary samples, as higher bacterial burdens within the specimen could potentially simplify the detection of the bac-teria in urine samples at the expense of the rest of the urinary proteome.…”
Section: Urinementioning
confidence: 99%
“…Prior to the use of MALDI-TOF MS for the diagnosis of UTIs, the presence of blood and bacteria in the urine was reported to interfere with urinary proteomic analysis, specifically altering key peptide-mass signals in the sample [24,25]. An additional report similarly suggested that bacterial overgrowth of the urine could hamper proteomic analysis, and recommended that samples be immediately centrifuged and stored at 4˚C, and have boric acid or sodium azide added to prevent bacteria from overgrowing [26]. Which specimen handling conditions are necessary for optimal identification of bacteria in urinary samples remains to be seen, as a high bacterial burden within urine samples could potentially simplify the detection of the bacteria at the expense of the rest of the urinary proteome.…”
Section: ) Urinementioning
confidence: 99%
“…During the storage, urinary samples might have bacterial overgrowth, which could change the urinary proteome [19]. Therefore, preservatives were recommended to prevent the bacterial overgrowth after collection [19].…”
Section: Preservativesmentioning
confidence: 99%